Dimensions of psychological problems : replacing diagnostic categories with a more science-based and less stigmatizing alternative - Lahey, Benjamin B. (New York, NY : Oxford University Press, 2021)
A manifesto for a remarkable revolution in thinking about psychological problems that is rapidly reaching a tipping point. Many psychologists and psychiatrists are proposing a far less stigmatizing understanding of mental health problems. Psychological problems are not terrifying'illnesses' of the mind but are problematic ways of thinking, feeling, and behaving that lie on dimensions from inconsequential to severe. Crucially, they are ordinary aspects of the human experience, both in the sense of being far more commonplace than previously believed and in arising through the same ordinary interplay of genetic and environmental influences as all behavior.
Also issued in print: 2021.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on September 2, 2021).
Keywords: Psychology, Pathological